Practice of non-financial reports assurance services in the Polish audit market: The range, limits and prospects for the future - Anna Bartoszewicz; Anna Rutkowska-Ziarko (Risks, 2021)
In recent years, many companies have been issuing non-financial information which is used by a wide range of stakeholders in their decision-making processes. Considering the fact that such reports play an important role in financial markets, the information they provide should be submitted to verification by an external, independent body. Our study, carried out in 2020, showed that only 2.3% of audit firms in Poland offer auditing non-financial report services. This was the starting point for our further investigations, the results of which will be presented in this article. The aim of the article is to identify the factors that limit or stimulate the performance of auditing in Poland with respect to non-financial data, and to determine the scope of operations carried out by audit firms which provide this service. The article comprises literature perusal and results of empirical studies among audit firms in Poland. Several important findings have emerged, including the fact that there are few companies in the Polish auditing market rendering the service of auditing non-financial reports, which are leaders in this field. The factor that most significantly limits the performance of non-financial report auditing is the low demand for such a service, which arises from the fact that verification and assurance of non-financial data are not obligatory for all reporting undertakings. Given that the number of CRS reports is increasing every year, it seems necessary to make full audits in order to confirm the reliability of non-financial information provided by reporting companies. Otherwise, stakeholders interested in these reports might be exposed to a risk of making inadequate decisions.
Keywords: 330; assurance; audit; CSR; Directive 2014/95/UE; non-financial reporting; sustainable development; sustainable risk; verification